PENGARUH PERSEPSI KEPEMIMPINAN KARISMATIK DAN MOTIVASI KEPALA SEKOLAH TERHADAP DISIPLIN KERJA GURU DI SEKOLAH TUGU IBU DEPOK - Sifah Fauziah; Lindiawatie Lindiawatie (Jurnal PROFIT: Kajian Pendidikan Ekonomi dan Ilmu Ekonomi, 2023)
Through field observations, problems were found related to the decline in teacher work discipline. Based on these facts, this research was carried out with the aim of finding out whether the decline in teacher work discipline was influenced by the variables of perception of charismatic leadership and motivation of school principals. The data collection method was by distributing questionnaires to 60 teacher respondents randomly. The results of the research show that the perception of charismatic leadership does not have a significant effect on teacher work discipline, the principal's motivation has a significant effect on teacher work discipline. Meanwhile, simultaneously the perception of charismatic leadership and the principal's motivation have a significant effect on teacher work discipline. The novelty obtained from this research is that if charismatic leadership is only a perception of subordinates, it will not encourage teacher work discipline. However, teacher discipline will be influenced by the motivation of the principal who is able to carry out true charismatic leadership.